2022
DOI: 10.1088/1742-6596/2265/4/042068
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of supersonic flow on wind turbines

Abstract: The future generation of wind turbines will be characterised by longer and more flexible blades. These large wind turbines are facing higher Reynolds numbers, as a consequence of longer chord lengths and increased relative wind speeds. Higher tip speeds, however, also result in an increased Mach number. Although the maximum tip speed in steady design conditions may remain (well) below the critical value, the presence of turbulence, wind gusts, blade deflections, etc. in combination with the flow acceleration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 13 publications
(16 reference statements)
1
10
0
Order By: Relevance
“…This turbine is strategically engineered using industry input to play a significant role in driving the ongoing evolution of next-generation wind turbine technologies. A recent study shows the potential occurrence of transonic flow under normal operational conditions, especially at cut-out wind speed, when the blade is pitched to large negative angles of attack, with shedding power in excess of rated conditions of the generator [8]. As the wind speed increases beyond rated wind speed, the blades adjust their pitch in order to maintain a rated power.…”
Section: Case Studymentioning
confidence: 99%
See 4 more Smart Citations
“…This turbine is strategically engineered using industry input to play a significant role in driving the ongoing evolution of next-generation wind turbine technologies. A recent study shows the potential occurrence of transonic flow under normal operational conditions, especially at cut-out wind speed, when the blade is pitched to large negative angles of attack, with shedding power in excess of rated conditions of the generator [8]. As the wind speed increases beyond rated wind speed, the blades adjust their pitch in order to maintain a rated power.…”
Section: Case Studymentioning
confidence: 99%
“…As the wind speed increases beyond rated wind speed, the blades adjust their pitch in order to maintain a rated power. [8], showed that close to cut out wind speed, the blades of the IEA 15WM reached high negative angles of attack. Figure 2 shows the operational conditions, in terms of inflow Mach number and angle of attack, in which transonic flow can occur for a given wind speed.…”
Section: Case Studymentioning
confidence: 99%
See 3 more Smart Citations